(untitled) (Revista Electrónica REDINE, 2021)
The purpose of this research, is to glimpse the senses and meanings that the workers of the Simón Rodríguez National Experimental University, Barquisimeto nucleus grant to ethical behavior and the development of virtues in the work environment. The theories that serve as the central axis of the investigation are: Aristotle’s ethics, which shows that human actions are directed towards the ultimate goal of achieving happiness, through the exercise of virtues; as well as the ethics of Thomas Aquinas who incorporates the theological virtues and explains the desire for perfection, through the existence of God. Theological virtue is particularly explored: love; from Scheler’s perspective, as a founding element of ethos. I also address the parallelism between human resource management by competencies with the Aristotelian virtues. Epistemologically, the research is based on the interpretive paradigm and thus reveals the experience of the staff in the exercise of virtues in the work environment; supported by hermeneutics, for interpretation from personal historicity. The research techniques and tools are participant observation, the discussion group and the interview, with a subjective, qualitative and holistic vision. Three (03) subjects were interviewed, their responses were analyzed before categorization by means of the Atlas-Ti. From the interpretation arises the relationship between ethics, virtues, love and happiness, a contribution to the paradigm of the whole person and the theoretical construct: The Virtue of Love in the Development of Other Virtues and Founder of Ethos for Human Talent Management.